Utilization of whey waste as a substrate for making nata de whey - Fina Ayu Tegarwati; Ana Fairuza Fajriana; Dwi Pujiana (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Increasing in demand and imports of cheese is parallel to an increase in cheese production annually. High cheese production is directly proportional to generation of whey. Whey is considered as wastewater and usually directly disposed to environment causing a detrimental impact such as water pollution. Whey contains 55% of dairy protein and is potential to be used for nata seed growth. Therefore, it is necessary to valorise whey into a high value-added product. This research aimed to use nutrient-rich whey wastewater as a medium of development for Acetobacter xylinum bacteria in the production of nata de whey, as well as to investigate the effect of of sucrose addition to the characteristics of nata de whey. The research design used was Randomized Block Design (RBD) with 2 factors of Acetobacter xylinum (inoculum) concentration (i.e. 5, 10, and 15%) and sucrose concentration (i.e. 3, 4, and 5%). The results showed that the treatment with addition of 10% inoculum and 4% sucrose produced the nata de whey with superior quality. The resulted nata de whey has pH of 3.2 ± 0.13, total sugar of 4.24 ± 1.11%, total acid of 1.67 ± 0.08%, yield of 84.41 ± 7.27%, thickness of 1.345 ± 0.18 mm, and moisture content of 83.4 ± 1.97%, respectively.